AKTIVITAS ANTIBAKTERI EKSTRAK KAYU SIWAK (Salvadora persica) TERHADAP BAKTERI Staphylococcus epidermidis - Nugroho Eko W B (Oceana Biomedicina Journal, 2021)
Background:Siwak is a plant that grows in the Arabian Peninsula which is used to clean teeth. Siwak has antibacterial properties because it contains flavonoids and alkaloids. This study aims to prove whether the extract of siwak stem powder can be used to inhibit the growth of Staphylococcus epidermidis bacteria Methods: In this study, using the Only Post Test Control Group Design method, namely pure experimental treatment and measuring the dependent variable. This study used 24 samples which were divided into four replications and six treatments. The study used extracts of siwak stems at concentrations of 25%, 50%, 75% and 100% and used clindamycin as a positive control and aquadest as a negative control. Research Results: The results showed that the average inhibition zones of siwak stem extract on the growth of Staphylococcus epidermidis from concentrations of 25%, 50%, 75%, and 100% were 0 mm, 0 mm, 10.01 mm and 14.65 mm. Conclusion: At a concentration of 75% ethanol extract of siwak stems, it was able to exert an inhibitory effect on the growth of Staphylococcus epidermidis bacteria but was still unable to match the inhibitory power of clindamycin.